Caregivers blinded by the care: A qualitative study of physical restraint in pediatric care - Lombart, Bénédicte (Nursing ethics, 2020)
Background:The phenomenon of forceful physical restraint in pediatric care is an ethical issue because it confronts professionals with the dilemma of using force for the child’s best interest. This is a paradox. The perspective of healthcare professional working in pediatric wards needs further in-depth investigations.Purpose:To explore the perspectives and behaviors of healthcare professionals toward forceful physical restraint in pediatric care.Methods:This qualitative ethnographic study used focus groups with purposeful sampling. Thirty volunteer healthcare professionals (nurses, hospital aids, physiotherapists, and health educators) were recruited in five pediatric facilities in four hospitals around Paris, France, from March to June 2013. The data were processed using NVIVO software (QSR International Ltd. 1999–2013). The data analysis followed a qualitative methodological process.Ethical Considerations:The research was conducted in compliance with the Declaration of Helsinki. Written informed consent was collected systematically from participants.Findings:This study provides elements to help understand why restraint remains common despite its contradiction with the duty to protect the child and the child’s rights. All participants considered the use of forceful physical restraint to be a frequent difficulty in pediatrics. Greater interest in the child’s health was systematically used to justify the use of force, with little consideration for contradictory or ethical aspects. Raising the issue of forceful restraint always triggered discomfort, unease and an outpour of emotions among healthcare professionals. The findings have highlighted a form of hierarchy of duties that give priority to the execution of the technical procedure and legitimize the use of restraint. Professionals seemed to temporarily suspend their ability to empathize in order to apply restraint to carry out a technical procedure. This observation has allowed us to suggest the concept of “transient empathic blindness.”Conclusion:Using physical restraint during pediatric care was considered a common problem by participants. This practice must be questioned, and professionals must have access to training to find alternatives to strong restraint. Conceptualizing this phenomenon with the concept of “transient empathic blindness” could help professionals understand what happens in their minds when using forceful restraint.